Antioxidant and anti-ageing activities of citrus-based juice mixture. (1st March 2016) - Kim, Dan-Bi; Shin, Gi-Hae; Kim, Jae-Min; Kim, Young-Hyun; Lee, Jin-Ha; Lee, Jong Seok; Song, Hye-Jin; Choe, Soo Young; Park, In-Jae; Cho, Ju-Hyun; Lee, Ok-Hawn
Highlights: We study the antioxidant and anti-ageing activities of citrus based juice mixture. The citrus based juice mixture treated group displayed enhanced antioxidant enzyme. Citrus based juice mixture suppressed the wrinkle formation in hairless mice. Citrus based juice mixture may be a functional drink to prevent oxidative stress. Abstract: The production of excessive reactive oxygen species by exposure to oxidative stress and solar radiation are primary factors in skin damage. We examined the effects of a citrus-based juice mixture and its bioactive compounds on antioxidant and anti-ageing activities in human dermal fibroblasts and hairless mice via the regulation of antioxidant enzymes and the mitogen-activated protein kinase pathway. The citrus-based juice mixture reduced H2 O2 -induced cell damage and intracellular reactive oxygen species production in human dermal fibroblasts. Citrus-based juice mixture pretreatment suppressed the activation of the H2 O2 -mediated mitogen-activated protein kinase pathway by activating the expression of activator protein 1 and matrix metalloproteinases. Moreover, it increased the expression levels of antioxidant enzymes such as glutathione reductase, catalase and manganese superoxide dismutase. In addition, oral administration of the citrus-based juice mixture decreased skin thickness and wrinkle formation and increased collagen content on an ultraviolet light B-exposed hairless mouse. These results indicate that the citrus-based juice mixture is a potentially healthy beverage for the prevention of oxidative stress-induced premature skin ageing.